2019
DOI: 10.1097/scs.0000000000005223
|View full text |Cite
|
Sign up to set email alerts
|

Fascia Lata Harvesting: The Donor Site Closure Morbidity

Abstract: Objective: Fascia lata (FL) is a worldwide adopted source of autologous grafts. In our Department, the endoscopic endonasal transphenoidal surgery (EETS) has been performed regularly for anterior and middle cranial fossa lesions, and FL graft has commonly been a practical resource in repairing tissue defects after EETS. Enough, we used routinely harvesting FL to restore symmetry in facial palsy. To our known, this is the biggest case series about FL harvesting to repare tissue defects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…While rare, more serious complications have been reported including long-term hypoesthesia and muscle herniation through the opening in the fascia. 27 Overall, our study demonstrated a success rate of 92% (46/50) in cases where FL was employed for reconstruction. It should be underscored that this was in the setting of complex defects and high-risk clinical scenarios, including predominantly high flow CSF leaks (and in the 10 cases of low flow CSF leak, all were associated with complicating factors), revision surgeries, expanded endonasal approaches, skull base malignancies, and previous or planned radiation therapy.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…While rare, more serious complications have been reported including long-term hypoesthesia and muscle herniation through the opening in the fascia. 27 Overall, our study demonstrated a success rate of 92% (46/50) in cases where FL was employed for reconstruction. It should be underscored that this was in the setting of complex defects and high-risk clinical scenarios, including predominantly high flow CSF leaks (and in the 10 cases of low flow CSF leak, all were associated with complicating factors), revision surgeries, expanded endonasal approaches, skull base malignancies, and previous or planned radiation therapy.…”
Section: Discussionmentioning
confidence: 51%
“…While rare, more serious complications have been reported including long-term hypoesthesia and muscle herniation through the opening in the fascia. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 43 44 45 46 47 48 Previous studies reported CSF leak in 0 to 58% of children who underwent tumor resection via EETS and it was successfully managed without further complications. 12 15 16 21 25 26 27 29 30 33 36 38 39 40 49 Intraoperative insertion of a lumbar drain prior to the resection and removing it at postoperative day 5 to 7 may minimize the risk of postoperative CSF leak. 6 50…”
Section: Surgical and Clinical Outcomesmentioning
confidence: 99%
“…18,[43][44][45][46][47][48] Previous studies reported CSF leak in 0 to 58% of children who underwent tumor resection via EETS and it was successfully managed without further complications. 12,15,16,21,[25][26][27]29,30,33,36,[38][39][40]49 Intraoperative insertion of a lumbar drain prior to the resection and removing it at postoperative day 5 to 7 may minimize the risk of postoperative CSF leak. 6,50 Endoscopic Endonasal Transsphenoidal Surgery versus Transcranial Approach Fahlbusch et al performed transsphenoidal surgeries in 29% of their patients.…”
Section: Visual Outcomesmentioning
confidence: 99%